Understanding and controlling the efficiency of Au24M(SR)18 nanoclusters as singlet-oxygen photosensitizers. Issue 13 (27th February 2020) - Agrachev, Mikhail; Fei, Wenwen; Antonello, Sabrina; Bonacchi, Sara; Dainese, Tiziano; Zoleo, Alfonso; Ruzzi, Marco; Maran, Flavio
Abstract : Atomically precise Au24 M(SR)18 clusters were used as singlet-oxygen photosensitizers. Comprehensive kinetic analysis provided insights into the mechanism and driving-force dependence of the quenching of 1 O2 by gold nanoclusters. Abstract : Singlet oxygen, 1 O2, can be generated by molecules that upon photoexcitation enable the 3 O2 → 1 O2 transition. We used a series of atomically precise Au24 M(SR)18 clusters, with different R groups and doping metal atoms M. Upon nanosecond photoexcitation of the cluster, 1 O2 was efficiently generated. Detection was carried out by time-resolved electron paramagnetic resonance (TREPR) spectroscopy. The resulting TREPR transient yielded the 1 O2 lifetime as a function of the nature of the cluster. We found that: these clusters indeed generate 1 O2 by forming a triplet state; a more positive oxidation potential of the molecular cluster corresponds to a longer 1 O2 lifetime; proper design of the cluster yields results analogous to those of a well-known reference photosensitizer, although more effectively. Comprehensive kinetic analysis provided important insights into the mechanism and driving-force dependence of the quenching of 1 O2 by gold nanoclusters. Understanding on a molecular basis why these molecules may perform so well in 1 O2 photosensitization is instrumental to controlling their performance.